2004
DOI: 10.1128/jcm.42.6.2733-2741.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of the Diagnostic Potential of Real-Time PCR, Double-Sandwich Enzyme-Linked Immunosorbent Assay for Galactomannan, and a (1→3)-β- d -Glucan Test in Weekly Screening for Invasive Aspergillosis in Patients with Hematological Disorders

Abstract: The establishment of an optimal noninvasive method for diagnosing invasive aspergillosis (IA) is needed to improve the management of this life-threatening infection in patients with hematological disorders, and a number of noninvasive tests for IA that target different fungal components, including galactomannan, (133)-␤-D-glucan (BDG), and Aspergillus DNA, have been developed. In this study, we prospectively evaluated the diagnostic potential of three noninvasive tests for IA that were used in a weekly screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
181
1
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(192 citation statements)
references
References 36 publications
6
181
1
4
Order By: Relevance
“…Similar results have been found by Maertens et al, Kawazu et al and Lai et al [14,15,16]. Cut off values have also been reviewed by Mycoses study group.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar results have been found by Maertens et al, Kawazu et al and Lai et al [14,15,16]. Cut off values have also been reviewed by Mycoses study group.…”
Section: Discussionsupporting
confidence: 79%
“…Next best cut off in our study was found to be ≥ 1.0 (Table 3). False positive cases were also low at cut off of 1.5 (12%).Similar results have been found by Maertens et al, Kawazu et al and Lai et al [14,15,16]. Cut off values have also been reviewed by Mycoses study group.…”
supporting
confidence: 74%
“…21 The prerequisite of two consecutive positive tests for IFD diagnosis was investigated in four studies and resulted in a specificity approaching 100% and a lower sensitivity ranging between 45 and 65%. 17,19,23,26 The diagnostic performance of BG was similar in IC and IA, while utility in other less common IFD could not be assessed because of lacking data. Few data on the timing of BG positivity compared with conventional diagnostic tools are available: one study suggested that BG detection might precede IFD diagnosis according to the EORTC/MSG criteria.…”
Section: B-glucan (Bg)mentioning
confidence: 99%
“…Overall, the results of cohort studies tend to exhibit a larger variability of test performance when compared with case-control studies. Different cutoffs for positivity have been investigated in seven studies, 17,[19][20][21][22]24,26 suggesting that the optimal cutoff if compared with the recommended value may be lower for the Wako and Maruha assays 19,26 and higher for the Fungitec-G assay. 21 The prerequisite of two consecutive positive tests for IFD diagnosis was investigated in four studies and resulted in a specificity approaching 100% and a lower sensitivity ranging between 45 and 65%.…”
Section: B-glucan (Bg)mentioning
confidence: 99%
See 1 more Smart Citation